Efficacy and safety of a novel anti‐HER2 therapeutic antibody RC48 in patients with HER2‐overexpressing, locally advanced or metastatic gastric or gastroesophageal junction cancer: a single‐arm phase II study. Issue 11 (19th October 2021) - Peng, Zhi; Liu, Tianshu; Wei, Jia; Wang, Airong; He, Yifu; Yang, Liuzhong; Zhang, Xizhi; Fan, Nanfeng; Luo, Suxia; Li, Zhen; Gu, Kangsheng; Lu, Jianwei; et al.
Abstract: Background: Current treatment options for human epidermal growth factor receptor 2 (HER2)‐overexpressing gastric cancer at third‐line have shown limited clinical benefit. Further, there is no specific treatment for HER2 immunohistochemistry (IHC) 2+ and fluorescence in‐situ hybridization‐negative patients. Here, we report the efficacy and safety of a novel anti‐HER2 antibody RC48 for patients with HER2‐overexpressing, advanced gastric or gastroesophageal junction cancer. Methods: Patients with HER2‐overexpressing (IHC 2+ or 3+), locally advanced or metastatic gastric or gastroesophageal junction cancer who were under at least second‐line therapy were eligible and received RC48 2.5 mg/kg alone every 2 weeks. The primary endpoint was the objective response rate (ORR) assessed by an independent review committee. Secondary endpoints included progression‐free survival (PFS), overall survival (OS), duration of response, time to progression, disease control rate, and safety. Results: Of 179 patients screened, 125 were eligible and received RC48 treatment. The ORR was 24.8% (95% confidence interval [CI]: 17.5%‐33.3%). The median PFS and OS were 4.1 months (95% CI: 3.7‐4.9 months) and 7.9 months (95% CI: 6.7‐9.9 months), respectively. The most frequently reported adverse events were decreased white blood cell count (53.6%), asthenia (53.6%), hair loss (53.6%), decreased neutrophil count (52.0%), anemia (49.6%), and increased aspartate aminotransferase level (43.2%). Serious adverse events (SAEs) occurred in 45 (36.0%) patients, and RC48‐related SAEs were mainly decreased neutrophil count (3.2%). Seven patients had adverse events that led to death were not RC48‐related. Conclusions: RC48 showed promising activity with manageable safety, suggesting potential application in patients with HER2‐overexpressing, advanced gastric or gastroesophageal junction cancer who have previously received at least two lines of chemotherapy. Abstract : RC48 is safe and efficacious for HER2‐overexpressing gastric cancer patients. Patients received trastuzumab showed similar efficacy with trastuzumab‐naïve patients. HER2 status doesn't have significant effect on clinical outcomes.